Pelung-Kampung Crosbred Chicken : Dietary Protein for 12 Weeks Old Meat Production - Iskandar, Sofjan (Indonesian Animal Sciences Society, 2006)
Increasing the utilization of local chickens has been put into national priority . Kampung chicken has been one of many local chickens used as a source of meat for consumption . Kampung chicken has actually an important role to rural community . Meat production of Kampung chicken is considerably low compared to modern selected broiler chicken . Pelung chicken is one of the local chickens, having larger body size that other local chickens . The crossing of Pelung male to Kampung female is one of the shortcuts in improving local chickens meat production . Pelung-Kampung cross could be a choice for commercial local meat type of chicken . Discussion is done on growth, carcass composition, body composition, and energy and nitrogen retentions. Keeping the bird up to 12 weeks of age with dietary protein of 21% for starter (0 - 6 weeks of age) followed by dietary protein 17% (6 - 12 weeks of age) resulted in the most economic return, but did not indicate a significant increase in biological variables . The rations with 19% dietary protein for starter followed by dietary protein of 15% for finisher up to 12 weeks of age were relatively a better choice of feeding strategy with lower input . Key words : Pelung x Kampung chicken, dietary protein, growth